Are you struggling? You need counselling: The growing trend of mental health contents on Instagram - Rismarini, Nadya Anjani (Psychological Research and Intervention, 2024)
Digital mental health platforms are increasingly emerging. These platforms provide psychological interventions and offer mental health-related content through their social media accounts on Instagram. While this content can raise awareness about mental health, it may also lead to misunderstandings and increase the risk of self-diagnosis. A recent study utilized content analysis to describe the characteristics of mental health-related content on Instagram. The results showed that the most dominant content category is romantic and family relationships, followed by life problems and psychological disorders, recovery and self-love, social media engagement, psychological knowledge, and finally, work and social relationships as the smallest category. Further investigation into science-based content is needed.